THE EFFECT OF LIST GROUP LABEL STRATEGY ON STUDENTS’ VOCABULARY MASTERY (A study at the Eighth Grade Students of MTs Darul Akhiroh Marancar in 2020/2021 Academic Year) - Winni Afryani Panjaitan (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract : The purpose of this research are to find out : 1) the extent of application of list group label strategy on students’ vocabulary mastery at the eighth grade of MTs Darul Akhiroh Marancar. 2) the extant of the students’ vocabulary mastery before and after using list group label strategy on students’ vocabulary mastery at the eighth grade of MTs Darul Akhiroh Marancar, 3) whether there is any significant effect of list group label strategy on students’ vocabulary mastery at the eighth grade of MTs Darul Akhiroh Marancar. The population of this research all of the eight grade students of MTs Darul Akhiroh Marancar consist of 24 students. The sample was 24 students which are taken by total sampling. The research method is used by experimental method. Then, the data collected by using the observation sheet and test. The instrument used is multiple choice. The calculation of t-test formula is higher than score of t-table. The score of t test is 3,13 meanwhile the score of t table is 2,07 at 5 % significant level with (df) 23. And the hypothesis is accepted. It means that there is a significant effect of list group label strategy on students’ vocabulary mastery at the eighth grade of MTs Darul Akhiroh Marancar in 2020/2021 academic year. Keywords: List Group Label Strategy, Vocabulary Mastery Abstrak : Tujuan dari penelitian ini adalah untuk mengetahui : 1) penarapan list group label strategy dalam penguasaan kosa-kata siswa kelas VIII MTs Darul Akhiroh Marancar, 2) mengetahui sebelum dan sesudah penggunaan list group label strategy dalam penguasaan kosa kata siswa kelas VIII MTs Darul Akhiroh Marancar, mengetahui apakah ada pengaruh yang signifikan dari list group label strategy terhadap penguasaan kosa-kata siswa kelas VIII MTs Darul Akhiroh Marancar Tahun Akademik 2020/2021. Populasi pada penelitian ini adalah seluruh siswa kelas VIII MTs Darul Akhiroh Marancar yang terdiri dari 24, teknik sampling yang digunakan adalah total sampling dengan jumlah 24 siswa. Metode penelitian digunakan adalah ekperimental method. Pengumpulan data menggunakan observation sheet dan tes sebagai instrument. Nilai rata-rata dari penerapan list group label strategy adalah 3.6, dengan kategori “ Sangat Baik”. peneliti menganalisis data menggunakan ttest formula, hasil ttest = 3.13 sedangkan ttable = 2.07. Dengan kata lain ttest lebih besar dari ttable. Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan dari list group label strategy dalam penguasaan kosakata siswa pada kelas VIII MTs Darul Akhiroh Marancar. Kata Kunci : List Group Label Strategy, Vocabulary Mastery